Aging and the Ethics of Authenticity. (2nd May 2017) - Laceulle, Hanne
Abstract: This article aims to make a philosophical contribution to debates about meaningful sociocultural narratives about aging. It is argued that the moral-philosophical discourse of authenticity may provide valuable resources for counter narratives about later life that are capable of challenging the dominant stereotyping decline- and age-defying cultural narratives. The discussion will draw on classical and contemporary views of authenticity by Rousseau; existentialists such as Kierkegaard, Nietzsche, and Heidegger; and contemporary thinkers such as Taylor and Meyers. Authenticity discourse is argued to be capable of, on the one hand, acknowledging the positive potentials of growth and development that later life may harbor, while, on the other hand, providing support for recognizing and integrating the inevitable existential vulnerability and finitude that old age also confronts us with. Although authenticity is not a commonly used term in gerontology, some examples show how a language associated with this philosophical discourse has found its way into gerontological thought as well, supporting its relevance for the context of aging. The article concludes with a discussion of four aspects through which the authenticity discourse may contribute to viable cultural narratives about later life.